2013
DOI: 10.4103/2230-8210.109667
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid ultrasound

Abstract: Thyroid ultrasonography has established itself as a popular and useful tool in the evaluation and management of thyroid disorders. Advanced ultrasound techniques in thyroid imaging have not only fascinated the radiologists but also attracted the surgeons and endocrinologists who are using these techniques in their daily clinical and operative practice. This review provides an overview of indications for ultrasound in various thyroid diseases, describes characteristic ultrasound findings in these diseases, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
83
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 22 publications
5
83
0
12
Order By: Relevance
“…[24] However, USG can not differentiate the lesions which are not surrounded by normal tissue. [24,25] Despite a significant increase in earlier stage diagnosis of thyroid cancer there is no decrease in mortality due to this disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] However, USG can not differentiate the lesions which are not surrounded by normal tissue. [24,25] Despite a significant increase in earlier stage diagnosis of thyroid cancer there is no decrease in mortality due to this disease.…”
Section: Discussionmentioning
confidence: 99%
“…[24] However, USG can not differentiate the lesions which are not surrounded by normal tissue. [24,25] Despite a significant increase in earlier stage diagnosis of thyroid cancer there is no decrease in mortality due to this disease. [27] Studies have suggested that there are more than 5% prevalence of thyroid nodules; whereas, investigators have shown more than 50 % of randomly selected population showed nodules in thyroid gland during ultrasonography.…”
Section: Discussionmentioning
confidence: 99%
“…УЗИ ЩЖ выполняли по стандартной методике [17]. В В-режиме измеряли линейные размеры долей ЩЖ с расчетом объема, оценивали ультразвуковые характеристики тканей ЩЖ.…”
Section: материалы и методыunclassified
“…При СDI оценивали васкуляризацию паренхимы. В режиме СDI+PWD определяли пиковую (систолическую) скорость кровотока (ПСК) в нижних тиреоидных артериях (НТА) и, посредством определения диастолической скорости кровотока (ДСК), индекс резистентности (ІR) (индекс Pourcelot) по формуле: ІR = (ПСК -ДСК) / ПСК [17]. Согласно данным различных исследователей, скоростные показатели кровотока в нижних и верхних тиреоидных артериях существенно не отличаются, потому для измерения скоростей и производных показателей мы ограничились правой и левой НТА [18].…”
Section: материалы и методыunclassified
“…У В-режимі вимірювали лінійні розміри часток ЩЗ з розрахунком об'єму, оцінювали ультразву-кові характеристики тканин ЩЗ. У режимі кольо-рового доплерівського картування (СDI) оціню-вали васкуляризацію паренхіми [21]. У дуплекс-ному режимі (СDI+PWD) визначали пікову сис-толічну швидкість (ПСШ) кровотоку в нижніх тиреоїдних артеріях (НТА) та посередництвом визначення діастолічної швидкості кровотоку …”
unclassified